A Noteon Dual Foreign Exchange Markets with official Rationing : Predetermined Versus Floating official Exchange Rate - Lizondo, Jose Saul (IMF Working Papers; Working Paper ;, 1991)
This paper examines the relationship between the long run rate of inflation and the allocation of transactions between markets in economies that operate dual exchange market regimes and ration foreign exchange in the official market. It shows that wider access of importers to the official market, and wider access of exporters to the free market, are associated with higher rates of inflation and vice versa. The direction of causality among the various variables, and thus the effects of economic policies, depend on whether the official exchange rate is predetermined or floating.